Law and the invisible hand : a theory of Adam Smith's jurisprudence - Malloy, Robin Paul, 1956- (Cambridge : Cambridge University Press, 2022)
A contemporary interpretation of Adam Smith's work on jurisprudence, revealing Smith's belief that progress emerges from cooperation and a commitment to justice. In Smith's theory, the tension between self-interest and the interests of others is mediated by law, so that the common interest of the community can be promoted. Moreover, Smith informs us that successful societies do at least three things well. They promote the common interest, advance justice through the rule of law, and they facilitate our natural desire to truck, barter, and exchange. In this process, law functions as an invisible force that holds society together and keeps it operating smoothly and productively. Law enhances social cooperation, facilitates trade, and extends the market. In these ways, law functions like Adam Smith's invisible hand, guiding and facilitating the progress of humankind.
Introduction : law's invisible hands -- Setting the stage -- Social organization in the informal realm -- Social organization in the formal realm -- Integrating the informal and formal in Smith's theory -- The spectator view -- Judgment and justice -- The sentiment of common interest -- The impartial spectator, homo-economicus, and homo-identitas -- Understanding the four stages of progress -- Adam Smith in American law -- Parting thoughts.
Title from publisher's bibliographic system (viewed on 07 Oct 2021).
Keywords: Law and econmics; Smith, Adam, -- 1723-1790 -- Influence